2018
DOI: 10.1002/anie.201809989
|View full text |Cite
|
Sign up to set email alerts
|

pH‐Dependent Degradation of Layered Black Phosphorus: Essential Role of Hydroxide Ions

Abstract: The practical application of layered black phosphorus (LBP) is compromised by fast decomposition in the presence of H2O and/or O2. The role of H2O is controversial. Herein, we propose a hydroxide ion (OH−)‐initiated degradation mechanism for LBP to elucidate the role of H2O. We found that LBP degraded faster in alkaline solutions than in neutral or acidic solutions with or without O2. Degradation rates of LBP increased linearly from pH 4 to 10. Density functional theory (DFT) calculations showed that OH− initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 42 publications
(18 reference statements)
4
63
0
Order By: Relevance
“…The C=Ns tretching vibrations also drifted to a higher wavenumber of about6cm À1 .T hese shifts in Raman stretches to ah igher wavenumbers trongly suggestst he formation of at hinner TAPB-PDA-COF structure. [16] Raman spectra of TAPB-PDA-COF monomers at different pH values are presented in Figure S6, Supporting Information, showing the TAPB-PDA-COF spectra are devoid of the TAPB and PDA characteristic peaks. FTIR spectra of TAPB-PDA-COF ( Figure S7, Supporting Information) and monomers ( Figure S8, Supporting Information)a td ifferent pH values also suggestst he TAPB-PDA-COF is stable and devoid of monomer characteristic peaks.…”
Section: Resultsmentioning
confidence: 99%
“…The C=Ns tretching vibrations also drifted to a higher wavenumber of about6cm À1 .T hese shifts in Raman stretches to ah igher wavenumbers trongly suggestst he formation of at hinner TAPB-PDA-COF structure. [16] Raman spectra of TAPB-PDA-COF monomers at different pH values are presented in Figure S6, Supporting Information, showing the TAPB-PDA-COF spectra are devoid of the TAPB and PDA characteristic peaks. FTIR spectra of TAPB-PDA-COF ( Figure S7, Supporting Information) and monomers ( Figure S8, Supporting Information)a td ifferent pH values also suggestst he TAPB-PDA-COF is stable and devoid of monomer characteristic peaks.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to this degradation mechanism, several other mechanisms have been proposed. Zhang et al [42] elucidated the role of OH − and H 3 O + ions on BP degradation by exposing BP to solutions of various pH values. The degradation rate was highest in an alkaline solution of pH 10 while decomposition slowed down in solutions of pH 4, indicating OH − ions accelerated Reproduced with permission.…”
Section: Role Of Oxygen and Watermentioning
confidence: 99%
“…The authors suggested that a similar interaction may be considered as the initial step in the experimentally observed degradation of the phosphorene sheet to molecular compounds such as hypophosphite or phosphate. 25 Fig . 5a and b show the optimized structures of the functionalized surface with oxygen and sulfur, respectively, obtained through solid state calculations by using the CRYSTAL17 package 26 using a supercell of 32 phosphorus atoms, namely P 32 , and one chalcogen atom.…”
Section: Extension Of the Chalcogen Transfer To The Phosphorene Surfacementioning
confidence: 99%